Survival of a Rifampicin-Resistant Pseudomonas fluorescens Strain in Nine Mollisols - Tami L. Stubbs; Ann C. Kennedy; Horace D. Skipper (Applied and Environmental Soil Science, 2014)
Pseudomonas fluorescens strain D7 (P.f. D7) is a naturally occurring soil bacterium that shows promise as a biological herbicide to inhibit growth of annual grass weeds, including downy brome (Bromus tectorum L.), in crop- and rangelands. Pseudomonas fluorescens strain D7rif (P.f. D7rif) is a rifampicin-resistant strain of P.f. D7. One of the greatest obstacles to successful biological weed control is survival of the organism under field conditions. Nine soils in the taxonomic order of Mollisols, collected from downy brome-infested areas of the Western and Central United States, were inoculated with P.f. D7rif and incubated in the laboratory to determine the effects of soil type, soil properties, incubation temperature, and soil water potential on survival of P.f. D7rif over 63 days. Silt loam soils from Lind, Washington, and Moro, Oregon, sustained the highest P.f. D7rif populations, and recovery was the lowest from Pendleton, Oregon soil. Survival and recovery of P.f. D7rif varied with soil type and temperature but not with the two soil water potentials tested. After 63 days, P.f. D7rif was recovered at levels greater than log 5.5 colony forming units (CFU) g−1 soil from five of the nine test soils, a level adequate to suppress downy brome under field or range conditions.